Notched strength of woven fabric kenaf composite plates with different stacking sequences and hole sizes - Romayne, Anders Hans; Ahmad, Hilton (EDP Sciences, 2016)
Advantages of using kenaf fibres over synthetic fibres in composites manufacturing are relatively cheap, less abrasive and hazardous during handling, and renewable materials. Current work investigates parametric effects on notched strength of woven fabric kenaf polymer composites plates with variation of lay-up types, notch sizes and plate thickness. Testing coupons are prepared using hand lay-up technique and circular notch were drilled prior to mechanical testing. Stress concentration at the notch edge promotes micro-damage event as tensile loading was applied leading to crack initiation and propagations across the plate width. It is suggested that woven fabric kenaf polymer composites are potentially used in low and medium load bearing applications.